Zhong Ri di fang zhi yu Jiang nan qu yu shi yan jiu - Wang, Weiping (Suzhou da xue chu ban she, 2014)
Abstract
Keywords: Historiography / China / History; Historiography / Japan / History; Historiography; Geschichte; Geschichtsschreibung; China, Southeast / History; China; China, Southeast; Japan; Jiangnan